African ancestry and innate immunity contribute to the incidence of multicentric Castleman's disease in HIV-1/Kaposi's sarcoma herpesvirus-coinfected individuals. (July 2012) - Westrop, Samantha J; Lagos, Dimitrios; Boshoff, Chris; Bower, Mark; Imami, Nesrina
Aims: Kaposi's sarcoma herpesvirus (KSHV) is the etiological agent of Kaposi's sarcoma and multicentric Castleman's disease (MCD), a lymphoproliferative disorder associated with high KSHV load. Here, we analyze the frequency of A299G, a TLR4 single nucleotide polymorphism associated with increased MCD incidence, in a cohort of HIV-1 + individuals, exploring the link between genotype, KSHV disease and ethnicity.Materials & methods: One hundred and seven HIV-1 + patients presenting with KSHV-related (n = 41) and KSHV-unrelated (n = 66) malignancies were analyzed according to ethnicity, and genotyped for A299G. DNA was extracted from peripheral blood, and the presence of A299G determined by pyrosequencing.Results: Of 41 patients presenting with KSHV-related malignancies, 12 were of African ancestry and 29 of European ancestry. MCD was diagnosed in 18 individuals, 50% of whom had African ancestry. HIV-1 + individuals with KSHV-related malignancies of African ancestry had a 2.4-fold increased occurrence of MCD compared with European counterparts (relative risk: 2.42; 95% CI: 1.28–4.55; p = 0.025). A299G was found to be present in 33% of black African and 10% of white European patients with KSHV-related malignancies. In the cohort of patients diagnosed with MCD (n = 18), A299G was present at a frequency of 0.33, regardless of ethnicity.Conclusion: The 2.4-fold higher incidence of MCD in patients of African ancestry presenting with KSHV-related malignancies may be due to the more than three-times higher frequency of A299G compared with that observed in European counterparts. This data highlights a clinically relevant consideration for those caring for KSHV + HIV-1 + patients of African ancestry, linking genetic variation to disease. Original submitted 25 April 2012; Revised submitted 10 May 2012